2022
DOI: 10.1515/revneuro-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and neuropsychological adverse effects of SARS-CoV-2 vaccines – where do we stand?

Abstract: The devastating characteristic of COVID-19 pandemic calls for immediate and effective solutions to tackle it. Vaccines seem to be the only promising and effective way to fight against the novel coronavirus – even against new mutated variants. Because of the rapid development and distribution of numerous COVID-19 vaccines in different platforms, meticulous evaluation of vaccines’ safety is more critical than ever – especially given the fact that most of the candidates have not completed the clinical phase. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 171 publications
1
5
0
Order By: Relevance
“…The current study revealed that most neurological AEFIs were more common in female with dyslipidemia, hypertension and diabetes mellitus in all three vaccine types, this finding is consistent with Dutch study which reported two-fold higher odds of having any AEFI as compared to males with most pronounced differences after the first dose and for nausea and injection site inflammation [10] . The most frequent clinical complaints of neurological AEFIs were numbness, headache and dizziness which are usually mild, short-duration, and self-limiting, similar to most studies [9] , [10] , [11] , [12] , [13] . Neurological AEFIs can be presented as the sole complaint or co-occurring with systemic AEFIs.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The current study revealed that most neurological AEFIs were more common in female with dyslipidemia, hypertension and diabetes mellitus in all three vaccine types, this finding is consistent with Dutch study which reported two-fold higher odds of having any AEFI as compared to males with most pronounced differences after the first dose and for nausea and injection site inflammation [10] . The most frequent clinical complaints of neurological AEFIs were numbness, headache and dizziness which are usually mild, short-duration, and self-limiting, similar to most studies [9] , [10] , [11] , [12] , [13] . Neurological AEFIs can be presented as the sole complaint or co-occurring with systemic AEFIs.…”
Section: Discussionsupporting
confidence: 57%
“…Bell’s palsy risk is slightly higher but the causality is not certain [16] . From most studies [11] , [12] , [13] , [14] , [15] , [16] , only a few serious neurological AEFIs occurred and were reported in isolated case reports or small case series. Many triggers coexist with vaccination which may lead to some serious neurological AEFIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study described that in febrile cases, the vaccine merely triggers seizures in patients with underlying genetic or structural defects [ 39 ]. In addition, seizures after COVID-19 vaccination commonly occur with other neurological conditions such as cerebral venous sinus thrombosis or vaccine-induced encephalopathy [ 40 ]. Given that our patient did not have neurological symptoms other than seizures, we could not conclude that the symptom was vaccine-related.…”
Section: Discussionmentioning
confidence: 99%
“…David Garcia-Azorin focuses on post-pandemic neurological syndromes (e.g., persistent headache ( 38 , 39 ) and insomnia ( 40 )). Nima Rezaei first mainly focused on neurological complications of COVID-19 ( 41 , 42 ) and then shifted to the neurological side effects of COVID-19 vaccination ( 43 ). Henrik Zetterberg focused on exploring potential neurochemical biomarkers and underlying mechanisms of COVID-19-related neuropathy ( 44 46 ), Tom Solomon was the most cited author because he published two articles in Lancet Neurology ( 3 ) and Lancet Psychiatry ( 5 ) that give readers a comprehensive understanding of the neurological and neuropsychiatric complications of COVID-19.…”
Section: Discussionmentioning
confidence: 99%